Probing fouling mechanism of anion exchange membranes used in electrodialysis self-reversible treatment by humic acid and calcium ions - M.A.C.K. Hansima (Elsevier, 2021)
When humic substances (HS) are present in the feed water, fouling of ion-exchange membranes is inevitable despite the built-in self-cleaning process of electrodialysis reversal systems (EDR). When Ca2+ is present in water, HS can readily chelate with them and form organic-Ca2+ complexes, which can foul anion exchange membranes (AEMs) in an irreversible manner. However, the elucidation of distinct processes between membrane scaling by Ca2+ and fouling by HS-Ca2+ complexes is debated. We examined the AEM fouling by Ca2+ and HS using synthetic groundwater. Well-characterized Sigma-Aldrich humic acid (HA) was used to adjust the dissolved organic carbon content in the water. Forcefully fouled AEM by HA and HA-Ca2+ was treated with 2% (w/w) NaCl and 0.03% (w/w) sodium dodecyl sulfate to destabilize the organic moieties on the membranes. The bonding types of HA-Ca2+ and HA with the membrane were examined by vibrational spectroscopy. The surface topographies were visualized by scanning electron microscopy. Both inter- and intramolecular interactions, including hydrophobic cation-π interactions among HA-Ca2+ complexes, were active in membrane fouling. Size compatibility and reduced surface charge of HA-Ca2+ (compared to HA) seems to alter the AEM self-cleaning process leading to irreversible fouling. Based on the vibrational spectral evidence, a plausible AEM fouling mechanism by HA-Ca2+ is proposed. Identification of interactions between the membrane and the foulant will provide an insight into designing appropriate self-cleaning protocols in EDR.